IPOs and equity offerings - Geddes, Ross (Global capital markets series., 2003)
An initial public offering (IPO) is one of the most significant events in corporate life. It follows months, even years of preparation. During the boom years of the late 1990s bull market, IPOs of growth companies captured the imagination and pocketbooks of investors like never before. This book goes behind the scenes to examine the process of an offering from the decision to go public to the procedures of a subsequent equity offering. The book is written from the perspective of an experienced investment banker describing the hows and whys of IPOs and subsequent equity issues. Each aspect of a.